2014
DOI: 10.1002/agr.21408
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Innovation Capacity Through Vertical, Horizontal, and Third‐Party Networks for Traditional Foods

Abstract: Across many sectors, the locus of innovation has shifted from the individual firm to networks of collaboration. Networking is one way for small‐ and medium‐sized enterprises (SMEs) in the food sector to cope with the many challenges they face with regards to innovation. In this article, we investigate the influence of different types of networking on the innovation capacity of chain networks in the traditional food sector. Our results highlight that networking among the vertical network members contributes mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 61 publications
0
23
0
1
Order By: Relevance
“…Whereas stable membership is important for producer groups to foster collective action on common interests, IPs warrant some fluidity in membership to remain dynamic forums where knowledge sharing generates fresh insights. Whereas horizontal networking can build farmer capacity through cooperation to address common problems or opportunities, linkages across the 'vertical networks', that bring different perspectives to a problem and different kinds of resources to an opportunity and that highlight the interdependence of actors, are of key importance for innovation and system change (Kebebe et al, 2015;Kuhne et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas stable membership is important for producer groups to foster collective action on common interests, IPs warrant some fluidity in membership to remain dynamic forums where knowledge sharing generates fresh insights. Whereas horizontal networking can build farmer capacity through cooperation to address common problems or opportunities, linkages across the 'vertical networks', that bring different perspectives to a problem and different kinds of resources to an opportunity and that highlight the interdependence of actors, are of key importance for innovation and system change (Kebebe et al, 2015;Kuhne et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Cluster membership within knowledge-intensive business services (KIBS) Asheim and Coenen 2005Regional innovation systems Fitjar and Rodriguez-Pose 2013Interaction-based innovation Schmitz (1985) Clusters of specialised firms Guiliani and Bell (2009) Evidence of clusters within the wine industry Kuhne et al, (2015); Menrad (2004) Collaborative 'food provision system' 2. Firms interact and share experiences and practice;…”
Section: Development Of Propositionsmentioning
confidence: 99%
“…Research within the food and agriculture sector has demonstrated the importance of collaboration amongst members of the food provision system, and close network linkages (e.g. Kuhne et al, 2015;Karantinis et al, 2010;Devaux et al, 2009;Fritz and Schiefer, 2008;Menrad, 2004). Table 1 provides an overview of key economic data indicators which shows the food industry as the largest manufacturing sector and clearly characterises it as a low technology sector.…”
Section: Introductionmentioning
confidence: 99%
“…For example, research findings indicate that farmers' adoption decision is based on economic motives (De Buck et al ., ; Pannell et al ., ) or, in the case of green innovations, on their environmental orientation and/or concern (Best, ; Mzoughi, ; Brudermann et al ., ). On the other hand, farmers' position in rural networks (Kühne et al ., ) and the level of information they have also play an important role (Wollni and Andersson, ; Yamada et al ., ), since innovation adoption is an information‐intensive decision. Another strand of research considers the associations between the adoption decision and farmers' demographic characteristics – such as gender (Doss and Morris, ; Burton et al ., ), age (Läpple et al ., ) and education (Gailhard et al ., ; He et al ., ) – or characteristics of the farm enterprise (Adesina, ; Mugonola et al ., ).…”
Section: On Farmers' Innovation Behaviormentioning
confidence: 99%